COMPARATIVE ANALYSIS OF LIQUEFACTION POTENTIAL USING THE SWEDISH WEIGHT SOUNDING TEST (SWST) AND N-SPT (GEOMATE Journal, 2024)
The assessment of liquefaction potential is an essential aspect of geotechnical engineering. However, the conventional Standard Penetration Test (SPT) often presents logistical and practical challenges, particularly in remote and inaccessible areas. As a result, there is growing interest in alternative methods, such as the Swedish Weight Sounding Test (SWST), which offers a more practical and economical approach to soil characterization. This study uses SWST and SPT to conduct a comparative analysis of liquefaction potential in the Gumbasa irrigation area, specifically in Petobo and Jono Oge, which are susceptible to earthquake-induced liquefaction. Two approaches were used, converting SWST data into equivalent SPT values through empirical correlations and directly utilizing SWST values to estimate liquefaction resistance, which were then compared to SPT-based procedures. In Petobo, the liquefaction resistance derived from empirical correlations shows a 7.18% difference, while the direct SWST approach yields resistance values 1.6 to 2.4 times higher than those from the SPT method. In Jono Oge, significant variations in liquefaction resistance were observed due to differences in soil resistance from the two techniques. However, in the topsoil, a minor gap of 1.54% was observed compared to the SPT method while using empirical correlations. The direct SWST method yielded values 0.87 to 1.48 times higher than those from the SPT. Overall, SWST shows promise for evaluating shallow liquefaction, though additional testing may be necessary for deeper layers. SWST can be a valuable and cost-effective method for preliminary liquefaction assessments, especially in areas where SPT is logistically challenging or expensive.